Natural parasitism by Synhimantus (Dispharynx) nasuta (Nematoda: Acuariidae) in captive Common Peafowl (Pavo cristatus) - Gómez-Puerta, Luis A. (2009)
The nematode Synhimantus (Dispharynx) nasuta (Rudolphi, 1819) Chabaud, 1975 parasiting the proventriculus of two chicks of Common Peafowl (Pavo cristatus Linnaeus, 1758) in captivity from Lima, Peru is described.